The Influence of Employee Commitment, Organizational Culture and Employee Spirit on Employee Performance MAXI Hotel Restaurant and Spa Legian in New Normal Living - Lindawati, Ni Putu; Ekadharma Susila, Bagus Putu (Akademi Komunitas MAPINDO, 2022)
This study aims to determine the effect of employee commitment, organizational culture and the spirit on employee performance at Maxi Hotel Restaurant and Spa Legian. Questionnaires are distributed to 94 respondents who are all members of the population. This study uses regression analysis techniques with hypothesis testing using T test and F test. The results of the T test shows that employee commitment has a positive and significant effect on employee performance at Maxi Hotel Restaurant and Spa Legian. This is proof by the results of the analysis showing the value of the regression coefficient X1(b1) tcount = 4.694 > ttable (0.05:89) = 1.66 and sig t = 0.002 (p < 0.05). Organizational culture has a positive and significant effect on employee performance at Maxi Hotel Restaurant and Spa Legian. This is proof by the results of the analysis showing the value of the regression coefficient X2(b2) tcount = 9.984 > ttable (0.05:89) = 1.66 and sig t = 0.000 (p <0.05). Morale has a positive and significant effect on the performance of Maxi Hotel Restaurant and Spa Legian employees. This is proof by the results of the analysis showing the value of the regression coefficient X3(b3) tcount = 11.987 > ttable (0.05:89) = 1.66 and sig t = 0.000 (p <0.05). Employee commitment, organizational culture and their morale have a positive and significant impact on the performance of Maxi Hotel Restaurant and Spa Legian employees. This is proof by the results of the analysis showing the regression coefficient value Fcount = 180,487 > Ftable (0.05:2:89) = 3.10 and sig F = 0.000 (p <0.05). The work spirit has variable on greatly influences the performance of Maxi Hotel Restaurant and Spa Legian employees with the largest Beta regression coefficient among other independent variables, namely 0.540, organizational culture variable with a value of 0.477 and employee commitment variable with a value of 0.320. Keywords: Employee Commitment, Organizational Culture, Work Spirit Employeeperformance